Sifat-Sifat Emulsi Susu Rekonstitusi yang Mengandung Mikrokapsul Minyak Ikan Kaya Asam Lemak w-3 - Teti Estiasih (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2006)
Fish-oil enrichment with w-3 fatty acids microcapsule is one way to increase food systems by w-3 fatty acids. Microcapsule containing fish oil enriched with w-3 fatty acids was produced by spray drying method. However its emulsifying properties in food systems had not been known. This research was conducted to elucidate the changes of protein emulsifying properties of reconstituted milk containing fish oil enriched with w-3 fatty acids The result showed that microcapsule addition onto reconstituted milk enhanced protein emulsifying properties as indicated by adsorbed protein, percentage of adsorbed protein, emulsifying activity index, interfacial area, protein load, and emulsion stability index. This was caused by caseinate in microcapsule had better emulsifying properties than protein in low fat milk.